2014
DOI: 10.1007/s11626-014-9826-2
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and miRNA-mediated posttranscriptional regulation of vitelline membrane outer layer protein I in the adult chicken oviduct

Abstract: The laying hen is the best model for oviduct growth and development. The chicken oviduct produces the egg components, including the egg white and eggshell. However, the mechanism of egg component production during oviduct development requires further investigation. Vitelline membrane outer layer protein 1 (VMO-1) is found in the outer layer of the vitelline membrane of avian eggs. Comparison of the chicken VMO-1 protein-coding sequence and the human, mouse, rat, and bovine VMO-1 proteins via multiple sequence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…It has been found in a previous study that the expression of VEGF is altered in the occurrence and development of AD, which may be associated with the disease process ( 4 ). Recently, the role of microRNA (miRNA) in post-transcriptional gene regulation has been uncovered ( 5 ). VEGF has been observed to be one of the targets of miRNA-210 ( 6 ), and a previous study has shown that the upregulation of miRNA-210 can increase the expression of VEGF in kidney tissue ( 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…It has been found in a previous study that the expression of VEGF is altered in the occurrence and development of AD, which may be associated with the disease process ( 4 ). Recently, the role of microRNA (miRNA) in post-transcriptional gene regulation has been uncovered ( 5 ). VEGF has been observed to be one of the targets of miRNA-210 ( 6 ), and a previous study has shown that the upregulation of miRNA-210 can increase the expression of VEGF in kidney tissue ( 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…As Klinge (2009, 2012) reviewed the role of the estrogen-regulated miRNA expression, E2 regulates selective miRNA expressions in female mammalian reproductive tissues. A recent study reported the E2-mediated regulation of miRNA in the chicken oviduct (In Lee et al, 2015). Therefore, the miRNA of the miRCN created in this study can be suggested to be the estrogen-mediated regulation factors in the induction of molting.…”
Section: Resultsmentioning
confidence: 99%